The Challenge of the Subject in the Face of the Real - Šerpytytė, Rita (Filosofia, 2023)
In one of her recent interviews, Catherine Malabou pointed out a problem which I deem to be pivotal in considering the question of the real with all its implications: speculative realists are indifferent to the subject. In this paper, I will present my position that in contemporary philosophy it is precisely the problem of the subject that becomes an actual challenge when raising the question “What kind of reality are we talking about?”; “What is real?” In light of treating the problem of the subject as a theoretical challenge in regard to the question of reality, two positions, that of Catherine Malabou (The New Wounded, Before Tomorrow) and Giorgio Agamben (Infanzia e storia), will be analysed and attempted to be compared. I will endeavour to discuss the problem how is the notion of the subject, the question of its identities, its transformations, being human-non-human, correlated to the question of reality.